Notas necrológicas: Dr. Celestino A. Danieli (1920-1987), Dr. Rafael Leoncio González (1924-1990) - Peña, Hugo A.; Porto, Juan C. (Acta Geológica Lilloana, 1992)
Dr. Celestino A. Danieli (1920-1987). Dr. Rafael Leoncio González (1924-1990).